Reticulocyte profile in top-level alpine skiers during four consecutive competitive seasons - Banfi, G.; Tavana, R.; Freschi, M.; Lundby, C. (European Journal of Applied Physiology, 2010)
The role of reticulocytes (Ret) in sports medicine became clear when the count of immature erythrocytes was introduced in protocols used for anti-doping purposes. Because specific research regarding seasonal variations in Ret is lacking, we assessed Ret (and [Hb]) in top-level male and female skiers during four consecutive competitive seasons. A difference (P < 0.05) between males and females was found for [Hb] and Ret values: [Hb] was lower and Ret was higher in females. The difference was maintained across all four competitive seasons. Marked within-subject differences in [Hb], Ret and immature reticulocyte fraction values were noted; the within-subject variability was greater than the between-subject variability in both genders. For instance, a difference for Ret was consistently shown between first and second blood drawings, i.e. between basal value, before the start of training and competition, and the value at middle of season, when training workload was at highest level. Unlike Ret%, the analysis of variance showed significant changes in [Hb] values across competitive seasons for both genders. Comparison between consecutive seasons (e.g., 2005-2006 vs. 2006-2007) showed significant differences for both parameters. The behaviour of [Hb] and Ret during the various seasons was parallel in females, whereas a discrepancy existed in males. In general, inter-individual variability is quite high, thus, Ret and [Hb] modifications should be referred only to the single athlete. We confirm the validity of the use of Ret counts for anti-doping purposes.